2006
DOI: 10.1143/jpsj.75.083708
|View full text |Cite
|
Sign up to set email alerts
|

Appearance of New Energy Gap and Periodic Local Density-of-States Modulation in Bi2Sr1.6La0.4CuO6+δ

Abstract: The spatial variation of the local density of states in optimally doped Bi 2 Sr 1:6 La 0:4 CuO 6þ (superconducting transition temperature is 34 K) is studied by scanning tunneling spectroscopy at 4.2 K in zero magnetic field. Two-dimensional density-of-states modulation aligned with the Cu-O-Cu bond with a periodicity of about five lattice constants is observed. It is found that this modulation accompanies the appearance of a new energy gap of approximately 10 meV, whose gap edge peak is spatially modulated in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 23 publications
6
30
2
Order By: Relevance
“…This phenomenon accounts for different charge fractions, 0.5 σ 0 for Bi-2212 vs. σ 0 for Tl-2212, and the marked dichotomy in T C0 . The same effect of electronegativity difference is found for the 2223 compounds (Bi,Pb) 2 . Conclusions are drawn in Section 5.…”
Section: Introductionsupporting
confidence: 73%
See 3 more Smart Citations
“…This phenomenon accounts for different charge fractions, 0.5 σ 0 for Bi-2212 vs. σ 0 for Tl-2212, and the marked dichotomy in T C0 . The same effect of electronegativity difference is found for the 2223 compounds (Bi,Pb) 2 . Conclusions are drawn in Section 5.…”
Section: Introductionsupporting
confidence: 73%
“…2 (∆T C0 ) k + t 0 , and where δ Tc is the standard deviation or width of the distribution and t 0 is an offset; N 0 ~ ±1 is the constant of integration. Fitting this model function for N k to the data yields the results δ Tc = 1.31(2) K, t 0 = 0.15 (2), and N 0 = 0.3 (4). The fitted model function is represented by the continuous solid curve in Fig.…”
Section: Accuracy In Calculated T C0mentioning
confidence: 98%
See 2 more Smart Citations
“…When the superconductivity is weakened, similar modulated patterns were observed in a zero magnetic field. [8][9][10]17) These ordered states may appear in the vortex core. Vershinin et al found a modulation in Bi 2 Sr 2 CaCu 2 O x above T c , that is, in the pseudo-gap state.…”
Section: )mentioning
confidence: 99%